The Concept of Moral Education According to Ibn Qayyim Al-Jawziyyah and Its Relevance to the National Education Objectives - Azhari, Amri Azhari; Saepudin, Didin; Husaini, Adian; Handrianto, Budi (TA`DIBUNA, 2026)
This study aims to examine the concept of moral education proposed by Ibn Qayyim al-Jawziyyah and to analyze its relevance to the objectives of Indonesia’s National Education system. The research is motivated by the moral decline among students in the modern era, which tends to prioritize scientific and technological advancement while neglecting moral and spiritual values. This study employs a library research approach, utilizing primary and secondary sources related to Ibn Qayyim al-Jawziyyah’s works. Data were analyzed using descriptive-analytical methods and content analysis. The findings reveal that Ibn Qayyim al-Jawziyyah’s concept of moral education centers on the purification of the heart as the foundation of character development. Moral education emphasizes tazkiyat al-nafs through the cultivation of universal values such as honesty, trustworthiness, inner peace, and social responsibility, integrated within theological, individual, and social dimensions. These findings indicate that Ibn Qayyim’s moral education framework plays a crucial role in shaping moral conduct in daily life. The study implies that Ibn Qayyim al-Jawziyyah’s concept of moral education is highly relevant and aligned with the goals of Indonesia’s National Education, particularly through a deep learning approach that focuses on developing learners who are faithful, pious, morally upright, and possess strong personal character.